2011
DOI: 10.1111/j.1863-2378.2011.01418.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Genetic Diversity of Campylobacter spp. in Domestic ‘Backyard’ Poultry in Canterbury, New Zealand

Abstract: Campylobacteriosis is the most commonly notified illness in New Zealand. Whilst the importance of commercial poultry in campylobacteriosis is well established, little is known about the possible role of chickens kept at home as a direct animal/faecal contact or consumption exposure pathway. The aim of this study was to determine the prevalence and genetic diversity of Campylobacter spp. in domestic backyard chicken flocks in the Canterbury region of New Zealand. Poultry faecal samples were collected from 35 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
1
23
2
Order By: Relevance
“…The prevalence of the thermotolerant species of Campylobacter found in this study (41.7%) was higher than the prevalence reported in Southern Chile (25.7%) by Fernández and Torres (2000) but lower to that informed in New Zealand, where 86% of flocks tested positive with a Campylobacter isolation rate of 57.7% (Anderson et al 2012). However, in agreement with the results of these authors, our isolation rate of C. jejuni was higher than the rate obtained for C. coli.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…The prevalence of the thermotolerant species of Campylobacter found in this study (41.7%) was higher than the prevalence reported in Southern Chile (25.7%) by Fernández and Torres (2000) but lower to that informed in New Zealand, where 86% of flocks tested positive with a Campylobacter isolation rate of 57.7% (Anderson et al 2012). However, in agreement with the results of these authors, our isolation rate of C. jejuni was higher than the rate obtained for C. coli.…”
Section: Resultscontrasting
confidence: 53%
“…However we could not obtain information from the owners about the use of antibiotics, we believe that as occurs in other places of the developing world, this probably reflects an overuse of these antibiotics in backyard chickens in this region, something that could represent an epidemiological problem with implications for treatment in human beings (WHO 2013, Whitehead andRoberts 2014). This is particularly important in backyard chickens because i) exposure of children to infected backyard poultry may represent another route of transmission for Campylobacter infection (Anderson et al 2012, Whitehead and Roberts 2014, El-Tras et al 2015, on which there are not sufficient epidemiological studies and ii) there is a lack of good biosecurity and good management practices applicable to reduce the risk of infection and antimicrobial resistance levels in backyard chickens (Whitehead andRoberts 2014, El-Tras et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, since only four birds were sampled per flock it is likely that there was misclassification with some infected flocks being defined as 'negative' on sampling results. Other exposure routes may also account for infection of these children namely ingestion of contaminated water, milk, food and exposure via other livestock or other households' backyard poultry [2,18,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Humans acquire Campylobacter infections chiefly through handling and/or consumption of contaminated food or drinks; mainly poultry, untreated water and unpasteurized milk [14,16,17]. Direct and indirect contact with infected animals (including poultry) and/or their faeces is also a risk factor for acquisition of infection by Campylobacter species [18]. In developing countries, Campylobacter infections occur most frequently in children as older children and adults acquire a level of protective immunity following exposure [9,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study reported by Abay et al (2014) in Turkey, 152 C. jejuni samples isolated from humans and chickens were analysed by PFGE; 81 of the isolates exhibited unique band patterns. Likewise, in a study by Anderson et al (2012), 168 C. jejuni and C. coli strains isolated from faeces of chickens exhibiting 34 different properties were analysed by PFGE, and a high diversity was found amongst the strains. Sma I/Kpn I PFGE analysis identified 50 different genotypes amongst the 168 isolated strains (Anderson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%